Writing changes alphabetic text and multimodal composition - Powell, Pegeen Reichert 1970- (Modern Language Association of America, 2020)
"Examines the relationship of multimodality and writing in composition studies, including considerations of composition as social practice and of changes to the conception of writing in relation to new social media and to writing program administration"--